The Effect of Eudamonic Value on Product Services, Satisfaction and Happiness of Foreign Tourists in Bali - Ariana, Nyoman; Antara, Made; Budiarsa, Made; Sudiarta, I Nyoman (E-Journal of Tourism, 2021)
There are various factors that cause tourists’ happiness. There are tourists who are happy because of the influence of hedonic, spiritual, social, cultural, psychological, economic, and including eudaimonic values. Of all the factors that cause happiness, one of the important factors that need to be explored in determining the happiness of foreign tourists is the eudaimonic value. For tourists, this eudaimonic value is related to various aspects of tourism services in the context of achieving happiness. Despite this, the effect of this eudaimonic value in particular on service products, satisfaction and happiness of foreign tourists when traveling to Bali is not yet clear. Having the background, the objective of this study is to prove the effect of eudaimonic value on product services, examine the effect of eudaimonic value on tourist satisfaction, prove the effect of product service on tourist satisfaction, and examine the effect of tourist satisfaction on the psychological happiness of foreign tourists in Bali. This study took a sample of 171 respondents, namely foreign tourists who traveled to Bali. The analysis method uses SEM (Structural Equation Model). Based on the results of the analysis, the research findings are as follows: the value of eudaimonic has a positive and significant effect on the service product, the value of eudaimonic has a positive and significant effect on tourist satisfaction, the service product has a positive and significant effect on tourist satisfaction, and tourist satisfaction has a positive and significant effect on tourist satisfaction. tourist psychology well-being. Based on the results of the four tests, these findings can formulate a model of eudaimonic tourist happiness in Bali which is acronymized with the term MTES (Model of Tourists Eudaiminic Happiness). The conclusion of this research is MTES which covers the happiness of foreign tourists in Bali consisting of aspects of eudaimonic value, the service product, tourist satisfaction, and psychology of tourist well being. This study has limitations in terms of the number of test variables because there are still relatively many variables as determinants of the happiness of foreign tourists who travel to Bali. For this reason, further research is recommended to test with other foreign tourists variables such as the characteristics of foreign tourists, length of visit, and the desire to visit again to test the happiness of eudaimonic tourists in Bali. Keywords: Eudaimonic, Service, Satisfaction, Happiness, Tourists